Kappa opioid receptors internalization is protective against oxygen-glucose deprivation through β-arrestin activation and Akt-mediated signaling pathway. (July 2020) - Xu, Jihong; Chen, Fang; Wang, Shuyan; Akins, Nicholas S.; Hossain, Md Imran; Zhou, Yi; Huang, Jinxi; Ji, Jiafu; Xi, Jin; Lin, Wenzhen; Grothusen, John; Le, Hoang V.; et al.
Abstract: Hypoxia induces reversible κ-opioid receptor (KOR) internalization similar to the internalization that is induced by KOR agonists. In the current study, we demonstrate that this KOR internalization is a protective mechanism via the β-arrestin specific pathway in an oxygen-glucose deprivation (OGD) model. Mouse neuroblastoma Neuro2A cells were stably transfected with mouse KOR–tdTomato fusion protein (N2A-mKOR-tdT cells). Various concentrations of salvinorin A (SA), a highly selective KOR agonist, were given in the presence and absence of norbinaltorphimine (norBNI), which is a KOR antagonist, or Dyngo-4a (internalization inhibitor) or API-2 (Akt/Protein kinase B signaling inhibitor-2). Various concentrations of SA and RB-64 (22-thiocyanatosalvinorin A, selective for the G protein signaling pathway) were administered both in normoxic and hypoxic conditions. Autophagosomes and ultrastructural components of cells were observed using transmission electron microscopy (TEM). Cell viability, severity of cell injury, and levels of proteins related to the Akt signaling pathway were evaluated using live cell counting (by Cell Counting Kit-8), the lactic acid dehydrogenase (LDH) release rate, and Western blot analysis, respectively. SA promoted cell survival and attenuated OGD-induced cell injury. The Akt signaling pathway is activated by SA. KOR internalization, when blocked by norBNI or Dyngo-4a, increased LDH release and decreased cell viability under OGD. Treatment with SA significantly inhibited autophagy, and the effects of SA on autophagy were reversed by API-2 pretreatment. RB-64 in a low concentration without β-arrestin recruitment did not reduce LDH release and increase cell viability as observed with SA. KOR internalization through β-arrestin activation is a protective mechanism against OGD. The Akt pathway might play a critical role in modulating these protective effects by inhibiting autophagy. Highlights: Both hypoxia and KOR agonists can induce a reversible KOR internalization. KOR internalization through β-arrestin activation is a protective mechanism toward oxygen-glucose deprivation induced injury. The Akt pathway might play a critical role in modulating these protective effects by inhibiting autophagy.